2022
DOI: 10.3389/fmed.2022.1016898
|View full text |Cite
|
Sign up to set email alerts
|

Small airways dysfunction in patients with systemic sclerosis and interstitial lung disease

Abstract: BackgroundA number of studies report small airways involvement in patients with systemic sclerosis (SSc). Furthermore, small airways dysfunction is increasingly recognized in patients with interstitial lung disease (ILD) of idiopathic or autoimmune etiology. The objectives of this study were to evaluate small airways function in SSc patients with ILD and explore the effect of treatment on small airways function by using conventional and contemporary pulmonary function tests (PFTs).MethodsThis single-center, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…There are only a few studies determining SAD in IPF patients' dysfunction by using either IOS [44] or spirometric results such as MMEF, FEF50%, FEF75%, FEV1%, and HRCT results [45,46]. At the same time, older studies have found histopathological evidence of SAD in IPF patients [42,47].…”
Section: Small Airways In Ipfmentioning
confidence: 99%
“…There are only a few studies determining SAD in IPF patients' dysfunction by using either IOS [44] or spirometric results such as MMEF, FEF50%, FEF75%, FEV1%, and HRCT results [45,46]. At the same time, older studies have found histopathological evidence of SAD in IPF patients [42,47].…”
Section: Small Airways In Ipfmentioning
confidence: 99%
“…Despite the recent advances in SSc-ILD treatment, lung involvement represents a fearsome manifestation of the disease, and the optimal timing to start an immunosuppressive and antifibrotic treatment still remains debated [6]. Recent studies also highlighted a certain involvement of a small airway in SSc patients, which may be associated with ILD [7]. A study on a Norwegian SSc cohort reported an ILD prevalence on HRCT (high-resolution computed tomography) of 50% [8].…”
Section: Introductionmentioning
confidence: 99%